THE DIGITAL AGENDA OF EAUE - Kushzhanov N.V.; Mahammadli Dashqin (Scientific Journal of Pedagogy and Economics, 2019)
The Eurasian Economic Union (EEU), created in 2015 by Russia, Kazakhstan, Kyrgyzstan, Belarus and Armenia, claims to be the first successful post-Soviet initiative to overcome trade barriers and promote integration in a fragmented, under-developed region. Supporters argue that it could be a mechanism for dialogue with the European Union (EU) and other international partners. Critics portray a destabilizing project that increases Russia’s domination of the region and limits its other members’ relations with the West. The EU views the project as a challenge to sovereign choices in its Eastern neighborhood. The purpose of the Eurasian Economic Union is comprehensive modernization, mutually beneficial cooperation, achievement of global competitiveness, economic growth and the quality life population improvement. One of the challenges on the way of digital economy development is providing security in cross-border purchases regarding giving guarantees for the protection of personal data of consumers. The EAEU plans to take the most successful experience of the history of the European Union and other integration associations in the formulation and implementation of the digital agenda, and then in building the digital economy. The Eurasian Economic Union (EAEU) is actively discussing the common digital agenda. The next step will be an elaboration of strategic initiatives in establishing the digital economy, so it is essential to understand what neighboring countries gained positive and negative experience.